Defining Terrorism: how Ambiguous Definitions and Vague Classifications Open Doors for Power Acquisition - Anastassiya Mahon (Master's Programs in International Relations, Faculty of Social and Political Science, Jenderal Achmad Yani University (UNJANI)., 2022)
In this article, I want to reflect on the difficulty of categorising the threat of terrorism within existing security frameworks and our theorising of threat assessment. As more types of terrorism get academic and political attention, various state and non-state actors use terrorist tactics or borrow some elements of terrorism to achieve their agenda. This article discusses the difficulties surrounding terrorist threat classification and how it perplexes our understanding of terrorism and counterterrorism. What have we learned over more than twenty years of researching terrorism? Terrorism is often conceptualised as both a traditional and non-traditional threat, complicating the execution of counterterrorism strategies. This ambiguity creates the need for a